Analysis and Modeling of Manufacturing Systems - Gershwin, Stanley B.; Dallery, Yves; Papadopoulos, Chrissoleon T.; Smith, J. MacGregor (International Series in Operations Research & Management Science, 2003)
Analysis and Modeling of Manufacturing Systems is a set of papers on some of the newest research and applications of mathematical and computational techniques to manufacturing systems and supply chains. These papers deal with fundamental questions (how to predict factory performance: how to operate production systems) and explicitly treat the stochastic nature of failures, operation times, demand, and other important events. Analysis and Modeling of Manufacturing Systems will be of interest to readers with a strong background in operations research, including researchers and mathematically sophisticated practitioners